POLYPHONY IN SABRI SILEVANI’S THE DOOR TO THE WORLD - SALIH, HUDA M. (Journal of Duhok University, 2023)
The current study aims at enriching the Kurdish literature and studies since it tackles a novel by a Kurdish writer. The study examines the features of a polyphonic novel, originated by the Russian literary critic and scholar, Mikhail Bakhtin, in Sabri Silevani’s novel, The Door to The World. Silevani is a writer from Duhok in The Kurdistan Region of Iraq. The research consists of two sections. The first section presents an over view of the concept of polyphony and its origin. As for the second section, it is divided into two subsections. The first one offers a short review of the novel, while the second section highlights the characteristics of a polyphonic novel as they appear in Silevani’s novel. The research ends with a conclusion that summarizes the main ideas discussed in the analysis of the novel